People's war variants and responses - Marks, Thomas A.; Rich, Paul B. 1950- (Routledge, 2018)
"Far from being an anachronism, much less a kit-bag of techniques, peoples war raises what has always been present in military history, irregular warfare, and fuses it symbiotically with what has likewise always been present politically, rebellion and the effort to seize power. The result is a strategic approach for waging revolutionary warfare, the effort "to make a revolution." Voluntarism is wedded to the exploitation of structural contradiction through the building of a new world to challenge the existing world, through formation of a counterstate within the state in order ultimately to destroy and supplant the latter. This is a process of far greater moment than implied by the label "guerrilla warfare" so often applied to what Mao and others were about. This volume deals with the continuing importance of Maoist and post-Maoist concepts of peoples war. Drawing on a range of examples that include Peru, Colombia, Bolivia, the Caucasus, and Afghanistan, the collection shows that the study of peoples war is not just an historical curiosity but vital to the understanding of contemporary insurgent and terrorist movements. The chapters in this book were originally published as a special issue of Small Wars & Insurgencies."--Provided by publisher.